The fourth horseman infectious diseases and the Philippine American War - Lozada, David Ozaraga III
"The study veers away from traditional politico-military narratives by demonstrating how infectious diseases like malaria, cholera and typhoid affected the conduct of military operations in Manila and the Island of Luzon during the Philippine-American War, 1899-1902. It also provides an epidemiological profile of the Philippines, particularly the city of Manila in the late 19th century, prior to the conflict with the United States. By looking at environmental, public health, economic and demographic factors and amalgamating it with the traditional military narrative, the study shows how a confluence of events created an environment that was conducive for the introduction and spread of infectious diseases in a time of war."